Analysis of Leadership, Digital Competence, Work Life Balance and Employee Experience on the Performance of Non-ASN Employees of Provincial Regional Financial and Asset Agencies North Sumatra - Nabillah; M. Chaerul Rizky; Emi Wakhyuni (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of leadership, digital competence, work life balance, and employee experience on the performance of non-ASN employees of the Regional Finance and Assets Agency of North Sumatra Province. The type of research used is quantitative research with a causal associative approach. The population in this study is all non-ASN employees of the Regional Finance and Assets Agency of North Sumatra Province totaling 54 people, using saturated sampling techniques so that the entire population is used as a research sample. The data collection technique used a questionnaire with a Likert scale, while the data analysis technique used multiple linear regression analysis with the help of SPSS software which included validity, reliability, classical assumption test, t-test, F test, and determination coefficient. Based on the results of the t-test (partial), it was shown that digital competence had a positive and significant effect on employee performance with a t-value of 4.218 and a significance of 0.001, making it the most dominant variable with a beta coefficient of 0.610. Work-life balance and employee experience also have a positive and significant effect on employee performance. Meanwhile, leadership had no significant effect on employee performance with a t-value of 1.902 and a significance of 0.063. The results of the F test (simultaneous) showed that the F value was calculated at 30.138 > F table 2.57 with a significance of 0.001 < 0.05, which means that leadership, digital competence, work life balance, and employee experience together have a significant effect on employee performance. The determination coefficient value (R²) of 0.711 or 71.1% showed that the variables of leadership, digital competence, work life balance, and employee experience were able to explain the variation in employee performance by 71.1%, while the remaining 28.9% were influenced by other variables that were not studied in this study.